Ratio of intestine length to body weight of giant gourami, Osphronemus goramy Lac. feed with different protein levels of the diets supplemented with recombinant growth hormone (rGH) - Darmawan Setia Budi; Alimuddin Alimuddin; Muhammad Agus Suprayudi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2016)
The purpose of this study was to describe the effect of dietary protein levels enriched with rGH on the ratio of length of the intestine to body weight of giant gourami. The diet with different protein levels (i.e. 21%, 28%, 34%; isoenergy) coated with egg yolk containing rGH. Each treatment has a control without rGH addition. Juveniles of giant gourami (body weight15.83 ± 0.13 g) were fed with a diet containing rGH twice a week. Fish were reared in 100 L glass aquaria with density of 10 fish per aquaria for 42 days. At the end of the treatment, body weight and length of the intestine were measured to determine the effect of treatment on the ratio of these two parameters. The result of research showed that at each level of treatment, the dietary protein levels and rGH supplementation gave a significant effect to increase the ratio of intestinal length to body weight (p <0,05). Ratio of intestinal length to body weight of fish was increase by decre-asing protein level in dietary (p <0,05). No interaction between protein levels and rGH additon on the ratio of intestinal length to body weight (p> 0,05). Abstrak Penelitian ini bertujuan untuk menjelaskan pengaruh pemberian pakan dengan kadar protein berbeda yang diperkaya dengan rGH pada nisbah panjang usus dan bobot tubuh ikan gurami. Pakan dengan kadar protein berbeda (21%, 28%, 34%;isoenergi) dibalut kuning telur yang mengandung rGH. Masing-masing perlakuan memiliki kontrol tanpa penam-bahan rGH. Yuwana ikan gurami (bobot tubuh15,83±0,13 g) diberi pakan mengandung rGH dua kali seminggu. Yuwa-na ikan dipelihara dalam akuarium volume100 L dengan padat tebar 10 ekor per akuarium selama 42 hari. Pada akhir perlakuan dilakukan pengukuran bobot tubuh dan panjang usus. Hasil penelitian menunjukkan bahwa pada masing-ma-sing taraf perlakuan kadar protein pakan, pemberian rGH berpengaruh nyata (p<0,05) terhadap peningkatan nisbah pan-jang usus dan bobot tubuh ikan. Penurunan kadar protein pada pakan terbukti meningkatkan nisbah panjang usus dan bobot tubuh ikan (p<0,05). Tidak terdapat interaksi antar perlakuan kadar protein dan penambahan rGH terhadap rasio panjang usus terhadap bobot tubuh (p>0,05).